2006
DOI: 10.1002/cncr.21854
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and immunomodulatory events after CTLA‐4 blockade with ticilimumab in patients with advanced malignant melanoma

Abstract: BACKGROUNDT‐regulatory (TR) cells expressing cytotoxic T lymphocyte‐associated antigen‐4 (CTLA‐4) maintain peripheral immune tolerance and negatively affect host immune responses against cancer. The immunobiologic effects of ticilimumab, a human monoclonal antibody against CTLA‐4, was administered to patients with metastatic melanoma who participated in a Phase I/II clinical trial.METHODSThirty patients who received ticilimumab at a dose of 10 mg/kg monthly (n = 20) or 15 mg/kg every 3 months (n = 10) were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
3
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 41 publications
(40 reference statements)
3
87
3
2
Order By: Relevance
“…It was reported that patients with objective response or disease stabilization had a decrease in CD4 ϩ /CD25 ϩ Treg cells and in constitutive IL-10 secretion compared with patients with progressive disease. However, functional assays were not reported [66]. In contrast, CTLA-4 blockade with ipilimumab did not alter the number or function of circulating Treg cells when tested by functional assays of suppressor activity (the gold standard for Treg cell quantitation) [44], mRNA levels of the Treg-specific transcription factor Foxp3 [67], and flow cytometric analysis of surface markers on Treg cells [26].…”
Section: Modulation Of Treg Cells After Administration Of Ctla-4 -Blomentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that patients with objective response or disease stabilization had a decrease in CD4 ϩ /CD25 ϩ Treg cells and in constitutive IL-10 secretion compared with patients with progressive disease. However, functional assays were not reported [66]. In contrast, CTLA-4 blockade with ipilimumab did not alter the number or function of circulating Treg cells when tested by functional assays of suppressor activity (the gold standard for Treg cell quantitation) [44], mRNA levels of the Treg-specific transcription factor Foxp3 [67], and flow cytometric analysis of surface markers on Treg cells [26].…”
Section: Modulation Of Treg Cells After Administration Of Ctla-4 -Blomentioning
confidence: 99%
“…Studies were conducted in a subset of patients within the Study 1002 phase II study to determine the potential role of modulating Treg cells on antitumor activity [66]. It was reported that patients with objective response or disease stabilization had a decrease in CD4 ϩ /CD25 ϩ Treg cells and in constitutive IL-10 secretion compared with patients with progressive disease.…”
Section: Modulation Of Treg Cells After Administration Of Ctla-4 -Blomentioning
confidence: 99%
“…The therapeutic efficacy of CTLA-4 blockade in murine models involves enhanced antitumor cytotoxicity, which reflects an increased proportion of CD8 ϩ T effector cells to FoxP3 ϩ Tregs within intratumoral infiltrates (12). Although CTLA-4 may contribute to Treg-induced immune suppression in some settings (13,14), the infusion of anti-CTLA-4 antibodies triggers an overall expansion of Treg numbers in tumor-bearing hosts, especially in regional lymph nodes (12). Thus, a complex dynamic between effector and regulatory pathways underlies the antitumor effects of CTLA-4 blockade.…”
mentioning
confidence: 99%
“…Tremelimumab is thought to stimulate patients' immune systems to attack their tumors. It has been shown to induce durable tumor responses in patients with metastatic melanoma in phase 1 and phase 2 clinical studies [44].…”
Section: Anti-ctla4 Antibodies: Ipilimumab and Tremelimumabmentioning
confidence: 99%